The Correlation Between Cooperative Learning Strategy and The Students’ Writing Ability of Procedure Texts at Class X RPL of SMK Negeri 6 Pekanbaru - Shayla Ega Renanda; Prih Febtiningsih; Pahmi Pahmi (Jurnal Pendidikan dan Sastra Inggris, 2025)
This research aims to examine the correlation between cooperative learning strategy and the students' writing ability of procedure texts at class X RPL of SMK Negeri 6 Pekanbaru. This research used a quantitative method by collecting data through questionnaires and writing tests, namely Cooperative Learning Strategy Questionnaire and Students' Writing Ability Of Procedure Text in Test Writing, to measure the correlation between these two variables. The results of the hypothsis analysis show that the significance value (2-tailed) from the t test is 0.000, which is smaller than 0.005. This shows that the null hypothesis (H0) is rejected, while the alternative hypothesis (Ha) is accepted. However, based on the correlation score classification of the two instruments, the average score is in the "Low" category, namely in the range 0.200 – 0.400. Therefore, it can be concluded that there is a correlation between cooperative learning strategy and students' writing ability of procedure texts, although the level of correlation is low.